2011
DOI: 10.1177/0883073811405203
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic and Neurobehavioral Sequelae in Children With Human Immunodeficiency Virus (HIV-1) Infection

Abstract: The range and extent of neurologic and neurobehavioral complications of human immunodeficiency virus (HIV-1) infection in children are under-described. Seventy-eight children with HIV-1 infection (32 females) were assessed for neurologic complications. Forty-six children had abnormal neurology examinations. Thirty-three children had global pyramidal tract signs, 5 had a hemiparesis, 4 had peripheral neuropathy, 18 had visual impairment, and 5 had hearing impairment. Thirty-nine of 63 children over 1 year of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
81
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 46 publications
(52 reference statements)
1
81
0
Order By: Relevance
“…Priorities under such circumstances are focused toward monitoring adherence with treatment protocols, disease complications, and medication side effects. 3 As previously reported, most children with seizures had generalized tonic-clonic seizures (67%). 4 On the basis of the multiple underlying pathologies, a greater proportion of focal seizures with or without loss of consciousness would be expected.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Priorities under such circumstances are focused toward monitoring adherence with treatment protocols, disease complications, and medication side effects. 3 As previously reported, most children with seizures had generalized tonic-clonic seizures (67%). 4 On the basis of the multiple underlying pathologies, a greater proportion of focal seizures with or without loss of consciousness would be expected.…”
Section: Discussionmentioning
confidence: 55%
“…28,29 In this study, the reported prevalence of 7.6% (95% confidence interval: 5.1-10.9%) of seizures in children with HIV is within the ranges reported in previous studies. [2][3][4][5][6] However, this figure may be an underestimate for a hospital-based population as the information was collated from retrospective data recorded by pediatricians in a busy outpatient setting. Priorities under such circumstances are focused toward monitoring adherence with treatment protocols, disease complications, and medication side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV-associated neurological complications are common in South African children and include a wide spectrum of disorders (Govender et al 2011). The specific consequences of HIV infection in the central nervous system (CNS) of vertically infected children could be associated with multiple factors.…”
Section: Introductionmentioning
confidence: 99%
“…[4] An SA study found the prevalence of neurological complications to be 59%, the most common being HIV encephalopathy and long-tract motor signs; however, no cases of cerebellar dysfunction were documented in that study. [4] The occurrence of ataxia in an HIV-positive individual is rare, with the chronic sequelae being neurocognitive impairment and polyneuropathy. [5] Ataxia in the setting of HIV is generally secondary to an infectious, vascular or neoplastic cerebellar lesion.…”
Section: Discussionmentioning
confidence: 75%